Implementasi Penjaminan Mutu Dalam Pengembangan Sumber Daya Manusia Pusat Ma’had Al-Jami’ah Universitas Islam Negeri - Khuluq, Iqomatu Nauvi (J-MPI (Jurnal Manajemen Pendidikan Islam), 2021)
This paper aims to reveal quality assurance in the development of human resources quality at the Center of Ma'had al-Jami'ah, Maulana Malik Ibrahim State University of Malang, with sub-focus covering: (1) the concept of quality standards (2) The process of implementing quality assurance conducted at the Center of Ma'had al-Jami'ah. This study used qualitative approach. Data collection is done by in-depth interviewing techniques participatory observation, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing, checking the validity of the findings carried out by extension of participation, source triangulation techniques, theories, and methods; and perseverance of the observer. The results showed that: 1) Quality standards were divided into three parts, namely standard input in the Center of Ma'had al-Jami'ah management, standard process in the Center of Ma'had al-Jami'ah management, and standard output in the Center of Ma'had al-Jami'ah management, 2) The process of implementing human resource quality standards is created by the establishment of Ma'had Ali, development programs consisting of Murobbi/ah resource development, Musyrif/ah resource development and talent interest development programs at the Center of Ma'had al-Jami'ah.